2019
DOI: 10.1080/20477724.2019.1670926
|View full text |Cite
|
Sign up to set email alerts
|

Entomological factors in relation to the occurrence of Japanese encephalitis in Malkangiri district, Odisha State, India

Abstract: Japanese encephalitis is a mosquito-borne arbo-viral disease with seasonal occurrence. Since 2009, AES/JE cases have been reported from Malkangiri district of Odisha State, India at an interval of one year.In the current study, the entomological parameters of known JE vector mosquito species were assessed for one year in Malkangiri district. Mosquito collections were done fortnightly in the index villages from August 2015 to July 2016 to record the density, their breeding habitats, feeding behaviour, parity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…fuscocephala , and Cx. pseudovishnui ) that also exhibit wide distribution across South and Northeast India(6,7). Given the wide range of suitable habitats for these mosquitoes, exposure to JEV vectors is extensive throughout the country.…”
Section: Introductionmentioning
confidence: 99%
“…fuscocephala , and Cx. pseudovishnui ) that also exhibit wide distribution across South and Northeast India(6,7). Given the wide range of suitable habitats for these mosquitoes, exposure to JEV vectors is extensive throughout the country.…”
Section: Introductionmentioning
confidence: 99%
“…So, for our study we have a total of (111,518 888)=99,027,984 mosquitoes. Another study carried out in some villages of Malkangiri district showed that 69.1% of available mosquitoes are vectors for JEV [22]. Hence, the total number of JEV vectors we have is N m =99,027,984 × 69.1%=68,428,337.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…We choose Malkangiri, the southern district of Odisha (Orissa) State in India. Malkangiri has a history of JE outbreaks since 2009 where the cases are documented as Acute Encephalitis Syndrome (AES) [22]. This AES can include infections other than JE.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations